1999
DOI: 10.2337/diabetes.48.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of ductal cells to cytokine responses by human pancreatic islets.

Abstract: In type 1 diabetes, autoimmune destruction of pancreatic beta-cells has been attributed to cytokines released from infiltrating immunocytes. Exposure of isolated islets to cytokines leads to nitric oxide (NO) production, which can damage beta-cells. Because ductal cells are closely associated with human beta-cells, we examined whether they can contribute to this process. Isolated human ductal cells were cultured for 48 h with various cytokines. The combination of interleukin-1beta (IL-1beta) plus interferon-ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 0 publications
4
58
1
Order By: Relevance
“…Previous studies have shown that exposure of duct cells to pro-inflammatory cytokines such as IFN-γ, either alone or in combination with IL-1β, led to their stimulation [1,3,4]. In particular, we recently observed that IL-1-exposed duct cells synthesise and release TNF-α (B. Movahedi, unpublished results).…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Previous studies have shown that exposure of duct cells to pro-inflammatory cytokines such as IFN-γ, either alone or in combination with IL-1β, led to their stimulation [1,3,4]. In particular, we recently observed that IL-1-exposed duct cells synthesise and release TNF-α (B. Movahedi, unpublished results).…”
Section: Introductionmentioning
confidence: 73%
“…It has been proven that both cytokines have direct and indirect toxic effects on beta cells through the induction of reactive oxygen intermediates and nitric oxide [4,38,39,40,41,42,43]. Besides its toxic effect, TNF-α could also influence adaptative immune responses directed against beta cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to know whether a similar process can occur in human islet grafts which are known to be heavily contaminated by pancreatic duct cells [19,20,21]. To investigate this possibility we prepared human pancreatic duct cells [22,23] and followed their cellular composition and cell population volumes over 10 weeks after transplantation in nude mice.…”
mentioning
confidence: 99%